SUSTENANCE OF HYGIENE PRACTICES THROUGH BEHAVIOR CHANGE MODEL INTERVENTION AT GENERAL PHYSICIANS’ CLINICS IN RAWALPINDI (The Research of Medical Science Review, 2024)
The main objective of the study was to measure the impact of the behavior change model during and after a COVID-19 wave during the pandemic through intervention (training and demonstration of hygiene practices) in patients reporting to general practitioners (GPs) clinics of Rawalpindi, It was a quasi-experimental study, the study was conducted in three GP clinics in Rawalpindi for ten months from August 2020 to May 2021, A total of 1026 participants aged 18-65 years were selected through a multistage sampling technique, from three GP clinics in Rawalpindi. Informed consent was taken and the purpose was explained ahead of data collection. Data was collected twice from the same participants using a self-structured pre-posttest tool that was pilot-tested before administration. The intervention comprised of demonstration of hand and respiratory hygiene principles and a health education/ awareness session in groups of 4-5 participants after the commencement of the pretest. The post-test was taken on the next visit of the respondents (minimum period of six weeks). Data was analyzed using SPSS 21, A total of 1026 adults from 3 clinics took part in this study, including 685 (66.8%) males & 341 (33.2%) females. The mean age of respondents was 33.72+11.20 years. The majority, 441 (43%) of them were laborers, & were illiterate 323 (31.5%). About 809 (79.04%) were married. The mean score of the participants’ hand hygiene responses was increased from 22.89+1.63 (pre-test) to 23.11+0.68 (post-test, significant at p< 0.05). The mean score of the participants’ respiratory hygiene responses was increased from 9.70+1.03 (pre-test) to 9.71+ 0.61(post-test, p= 0.643, non-significant), There was a statistically significant gain in mean scores of responses related to hand and respiratory hygiene behavior, after the intervention of the behavior change model through health education sessions. No significant change was observed in knowledge regarding the COVID-19 infection.